2022
DOI: 10.1021/acsmeasuresciau.2c00041
|View full text |Cite
|
Sign up to set email alerts
|

Probing Individual Particles Generated at the Freshwater–Seawater Interface through Combined Raman, Photothermal Infrared, and X-ray Spectroscopic Characterization

Abstract: Sea spray aerosol (SSA) is one of the largest global sources of atmospheric aerosol, but little is known about SSA generated in coastal regions with salinity gradients near estuaries and river outflows. SSA particles are chemically complex with substantial particle-to-particle variability due to changes in water temperature, salinity, and biological activity. In previous studies, the ability to resolve the aerosol composition to the level of individual particles has proven necessary for the accurate parameteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 162 publications
(448 reference statements)
2
5
0
Order By: Relevance
“…In recent years, SEM-EDX has emerged as an important tool in offline particle analysis for characterizing the elemental composition within individual particles. , Figure A shows a representative core–shell with internal mixing containing a prism core and a shell of organic carbon where the core is characterized as sodium chloride (NaCl), with a Cl/Na ratio ranging between 0.4 and 0.8. This ratio is smaller than what is typically observed in seawater (1.2–1.8), suggesting a depletion of chloride ions (Cl – ) may have occurred during and after sampling. ,, Additionally, a slight increase in magnesium (Mg) around the core indicates a possible coating of magnesium chloride (MgCl 2 ), which is consistent with previous studies conducted on SSA core–shells. ,, Rounded particles (Figure B) exhibited a high carbon content, which is often associated with organic carbon. Previous studies have reported that some rounded particles possess a carbon coating with a sulfur-rich core, but these types of particles were not observed in the current analysis. ,, Figure C shows rod inclusion core–shells which contain a NaCl core, organic shell, and rods with elevated counts of oxygen, sulfur, calcium, and magnesium.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…In recent years, SEM-EDX has emerged as an important tool in offline particle analysis for characterizing the elemental composition within individual particles. , Figure A shows a representative core–shell with internal mixing containing a prism core and a shell of organic carbon where the core is characterized as sodium chloride (NaCl), with a Cl/Na ratio ranging between 0.4 and 0.8. This ratio is smaller than what is typically observed in seawater (1.2–1.8), suggesting a depletion of chloride ions (Cl – ) may have occurred during and after sampling. ,, Additionally, a slight increase in magnesium (Mg) around the core indicates a possible coating of magnesium chloride (MgCl 2 ), which is consistent with previous studies conducted on SSA core–shells. ,, Rounded particles (Figure B) exhibited a high carbon content, which is often associated with organic carbon. Previous studies have reported that some rounded particles possess a carbon coating with a sulfur-rich core, but these types of particles were not observed in the current analysis. ,, Figure C shows rod inclusion core–shells which contain a NaCl core, organic shell, and rods with elevated counts of oxygen, sulfur, calcium, and magnesium.…”
Section: Resultssupporting
confidence: 87%
“…This ratio is smaller than what is typically observed in seawater (1.2−1.8), suggesting a depletion of chloride ions (Cl − ) may have occurred during and after sampling. 41,83,84 Additionally, a slight increase in magnesium (Mg) around the core indicates a possible coating of magnesium chloride (MgCl 2 ), which is consistent with previous studies conducted on SSA core−shells. 41,85,86 Rounded particles (Figure 6B) exhibited a high carbon content, which is often associated with organic carbon.…”
Section: Scanning Electron Microscopy-energy Dispersive Xray Spectros...supporting
confidence: 90%
See 2 more Smart Citations
“…This allows for the identication of different chemical species and phases present as well as a way to distinguish some of the unique "local environments" due to hydration, complexation, different phases, and other chemical and physical heterogeneities within environmental systems. 26,27 By monitoring the peak position, shape, and intensity of vibrational bands, molecular level insights can be gained. While a great deal of the current literature has used different vibrational methods, the recent development of micro-spectroscopic probes has been found to provide information on much smaller length scales.…”
Section: Introductionmentioning
confidence: 99%